Pengaruh Pendekatan Bermain Terhadap Keterampilan Passing Bawah Bola Voli Pada Ekstrakurikuler Sma Negeri 1 Sompak : Penelitian - Damianus Darmo; Fitriana Puspa Hidasari; Witri Suwanto; Mimi Haetami; Doni Pranata (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to determine the effect of the playing approach on volleyball underhand passing skills in students participating in extracurricular activities at SMA Negeri 1 Sompak. This study used an experimental method with a one-group pretest–posttest design. The sample of the study was 20 volleyball extracurricular students selected using a total sampling technique. The research instrument used was a volleyball wall pass test to measure underhand passing skills at the pretest and posttest stages. The results showed an increase in underhand passing skills after the application of the playing approach. The average pre-test score was 12.55 and the post-test 17.25 with a difference of 4.7, with a percentage increase tested using the effect size test of 37.45%. The results of the normality test showed that the data were normally distributed, then the homogeneity test showed that the data were homogeneously distributed as evidenced by the results of 0.531> 0.05 while the t-test produced a significance value of 0.000 (<0.05), which means there was a significant difference between the pre-test and post-test results. It can be concluded that the playing approach has a positive effect on improving volleyball underhand passing skills.